The Implementation of Oil and Gas Cooperation Contract Based on the Legal Principles of Pacta Sunt Servanda and The States Right to Control Land, Water and Natural Wealth Pursuant to Article 33 Paragraph (3) of The 1945 Constitution of The Republic of - Fully Handayani Ridwan (Universitas Muhammadiyah Sumatera Utara, 2023)
The legal relationship that is born from the oil and gas contract is binding as law for the parties who make it. This is because the formation of oil and gas contracts is in accordance with Article 1320 of the Civil Code and therefore based on Article 1338 paragraph (1) of the Civil Code, the government and contractors are legally bound to comply with all provisions in the oil and gas contract. However, considering the fact and investment sentiment towards the oil and gas industry in Indonesia that is decreasing, especially regarding investor confidence in legal certainty in Indonesia, it is necessary to have a significant increase and improvement in oil and gas contracts in Indonesia. Managing upstream business activities using a contract system has its own peculiarities because the upstream oil and gas business has many risks and given that the government also has many limitations. Another peculiarity is that in the oil and gas contract, one of the parties is the government which is constitutionally in the realm of private and public law simultaneously. The juridical question here is, what is the impact of the position of the Government as a party to an agreement that can change the laws and regulations in the oil and gas sector which results in the certainty of oil and gas contracts and justice for the parties? What is the ideal oil and gas contract that puts the parties in a balanced position? This dissertation will look at how the application of laws and regulations, both in the fields of public law and civil law, in oil and gas contracts and find out why legal uncertainty in the application of oil and gas contracts is still a problem today. In addition, this dissertation discusses the application of oil and gas contracts and examines the legal relationship that has occurred so far and looks for ideal points from oil and gas contracts from both government and private parties. The research will be conducted using the juridical normative research methodology and the data collected is secondary data (consisting of primary, secondary and tertiary legal materials). In conclusion, in the implementation of oil and gas contracts, apart from the level of implementation, there are several legal restructurings that can have an impact on the creation of a better legal relationship between the government and oil and gas contractors in implementing oil and gas contracts.